The Effectiveness of Cognitive-Behavioral Therapy on Resilience in High School Students - Mohammad Firoozmokhtar; Mozgan Arefi; Mohsen Golparvar (Iranian Evolutionary Educational Psychology Journal)
Objective: The enhancement of resilience, a psychological characteristic, can be achieved through addressing the various challenges and issues faced during adolescence. Methods: Consequently, this study aimed to investigate the impact of Cognitive Behavioral Therapy (CBT) on the resilience levels of high school students. Employing a semi-experimental design with a pre-test and post-test, as well as a control group, the research encompassed a 90-day follow-up period. From a pool of 10th and 11th grade students, 30 participants were randomly selected and assigned to either the experimental or control group, with each consisting of 15 individuals. The experimental group underwent 12 sessions of 90-minute cognitive-behavioral therapy. Throughout the study, the research participants completed Connor and Davidson's resilience questionnaire on three occasions: pre-test, post-test, and follow-up. The data obtained were subjected to analysis using repeated measures analysis of variance and analysis of covariance. Results: Notably, the application of cognitive-behavioral therapy yielded a significant improvement in the resilience of high school students (p<0.001). Conclusions: Consequently, this study demonstrates the potential of cognitive-behavioral therapy as an effective intervention for enhancing the resilience of high school students